Towards A 21st Century Systematize the Ideas; COVID-19, Sustainability and Discourse of SDG, (Sustainable Development Goals), The Cities and Housing Models - Coskun, Hülya (Archives of Case Reports, 2024)
The research creates a theoretical basis for examining the metamorphic changes and transformations in urban and housing planning with the interaction created by the latest epidemic in the world, which is moving towards a period related to climate problems. The first quarter of the 21st century witnessed an unexpected event: Humanity found itself in the middle of a pandemic considered temporary, it would be permanent and change the world dramatically. The post-COVID-19 period has led to significant and permanent changes in our lives, from urban planning to housing typologies. The study aims to understand the changing dynamics in the post-pandemic period that converges on the same goal with SDG, (Sustainable Development Goals), as continuity by updated dialogues, and discourses on literature. This research focuses on the SDG, (Sustainable Development Goals), and the post-pandemic period, analysis of two phenomena separated, analogous paradigms or intertwined. The findings of the public perception are there is a distinction between sustainability and pandemics considered dissimilar processes, they contain similarities. Contrary to common ideas, the pandemic was a catalyst for sustainability, and these two concepts contain analogous ideas and principles. In conclusion, it is revealed that they both concentrated on similar ideas; SDG, (Sustainable Development Goals) is “health”, and pandemic is the “healthy city” concept like; clean air, zero carbon, living healthy and safely in airy and green areas, etc.